2022
DOI: 10.1186/s12871-022-01783-6
|View full text |Cite
|
Sign up to set email alerts
|

Procedural analgesic interventions in China: a national survey of 2198 hospitals

Abstract: Background Humane treatment requires the provision of appropriate sedation and analgesia during medical diagnosis and treatment. However, limited information is available about the status of procedural analgesic interventions in Chinese hospitals. Therefore, a nationwide survey was established to identify challenges and propose potential improvement strategies. Methods Forty-three members of the Pain Group of Chinese Society of Anesthesiology estab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 43 publications
0
0
0
Order By: Relevance
“…The increased satisfaction scores reflect this among patients based on their perceived quality and readiness to undergo another procedure whenever needed. It has been furtherly demonstrated that such effectiveness is usually associated with increased surgical, scientific, and clinical quality based on gastroenterologists' perspective because they can better perform upper and lower exploration procedures, which have been associated with improved adenoma resection rates and enhanced main quality indices [129][130][131][132][133]. However, besides the issues mentioned above, the effectiveness of sedation during digestive endoscopies might also be burdened by financial costs.…”
Section: Costs and Economic Issuesmentioning
confidence: 99%
“…The increased satisfaction scores reflect this among patients based on their perceived quality and readiness to undergo another procedure whenever needed. It has been furtherly demonstrated that such effectiveness is usually associated with increased surgical, scientific, and clinical quality based on gastroenterologists' perspective because they can better perform upper and lower exploration procedures, which have been associated with improved adenoma resection rates and enhanced main quality indices [129][130][131][132][133]. However, besides the issues mentioned above, the effectiveness of sedation during digestive endoscopies might also be burdened by financial costs.…”
Section: Costs and Economic Issuesmentioning
confidence: 99%